The Effect of Endorsement and Product Quality on Brand Image and Its Implication on Customer Loyalty of Fashion Product - Erlin Dolphina; Ika Baskara; Prety Diawati; Husnawati Rachman; Susanti Budiastuti (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The Covid-19 pandemic, which has hit the whole world and brought about economic downturn in various business fields, has not reduced consumer interest in shopping for fashion products. One of the fashion products that has actually experienced an increase in business in recent times is the Erigo fashion brand. This research aims to analyze the effect of endorsement and product quality on brand image and its impact on consumer loyalty. This quantitative research involved 100 respondents who use Erigo fashion products as a sample selected by purposive sampling method. The data obtained from the respondent's questionnaire were processed using correlation and regression tests using SPSS 22 software. The results of this study indicate that the researcher's hypothesis is proven. Even though the endorsement and product quality have an effect on Erigo's fashion products, this brand is not quite right at targeting the appropriate consumer targets, so that the brand image displayed is less able to be captured by consumers. If this brand image can be improved in the future, customer loyalty can increase significantly